Penggunaan Kontrasepsi terhadap Gangguan Siklus Menstruasi di BPM A: Use of Contraceptives for Menstrual Cycle Disorders in BPM A - Anastasia Anugrah Susilaningrum; Uci Ciptiasrini; Madinah Munawaroh (Jurnal Interprofesi Kesehatan Indonesia, 2022)
Introduction: Indonesia, with a very large population, is committed to implementing the Planning Family and Birth Control as a means of fulfilling international demands in improving the lives of mothers and children. One of the problems with the family planning program is menstrual disorders due to the use of hormonal contraceptives such as a one-month injection and three months of injection contraception, which often become complaints from family planning acceptors. Objectives: The purpose of this study was to determine the difference in the shortest and longest cycle length between the two types of hormonal injection contraception. Method: This research is a cross-sectional study conducted at the Midwife Practice Anastasia Ningrum with samples in the form of hormonal injection family planning acceptors from January 2020 to June 2020 with a sampling technique in the form of accidental sampling. The inclusion criteria in this study were active injection family planning acceptors and had an FP control card with the exclusion criteria in the form of injection contraceptive use ≤ 6 months. The independent variable in this study was the use of 1 month and three months of injection contraceptive, while the dependent variable was the shortest and longest menstrual cycle length. Result: The results of this study involved 70 respondents with the shortest cycle length for injection contraception of 1 month and three months, respectively 28 (21 - 40) days and 60 (28 - 90) days, as well as the longest cycle lengths for injection contraception of 1 month and three months respectively. count is 35 (28 - 90) days and 90 (40 - 90) days. The mean difference between groups using the Mann Whitney test was significant for both the longest cycle and the shortest cycle (p-value <0.05). Conclusion: There was a significant difference between the longest and the shortest cycle length between 1 month and three months of injection contraceptive use.